2021
DOI: 10.1038/s41598-021-98451-5
|View full text |Cite
|
Sign up to set email alerts
|

Galvanic current dosage and bacterial concentration are determinants of the bactericidal effect of percutaneous needle electrolysis: an in vitro study

Abstract: Percutaneous needle electrolysis (PNE) is a physiotherapy technique that has been shown to be effective in different pathologies such as tendinopathies or mammary fistula. For many years, theoretical bactericidal and germicidal effects have been attributed to this type of galvanic currents, partly explained by the changes in pH that it generates. However, these effects have not yet been demonstrated. The aim of this study was to evaluate the bactericidal effect and the changes in pH caused by PNE. S. aureus we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…Based on the results obtained, the needle gauge seems not have a lineal relationship with the level of bacterial death. Our results with needles of the smallest gauge were similar to previous in vitro studies that found good results using acupuncture needles (0.30 mm × 30 mm) with current doses of 0.125 C 14 . This equivalence between studies strengthens our affirmation.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Based on the results obtained, the needle gauge seems not have a lineal relationship with the level of bacterial death. Our results with needles of the smallest gauge were similar to previous in vitro studies that found good results using acupuncture needles (0.30 mm × 30 mm) with current doses of 0.125 C 14 . This equivalence between studies strengthens our affirmation.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, since we found that the bactericidal effect does not depend on the needle gauge, we could use NE in pathologies of multiple locations and different sizes, from mammary fistulas which can have a different diameter and volume 16 , 17 , to hidradenitis suppurativa which are usually located in small areas of the armpits or inguinal fold 22 . In addition, since previous authors 14 have pointed out that it can have a needle dragging effect in percutaneous applications, these findings offer greater safety to this novel technique.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations